Implementasi Peran Guru PAI Dalam Membangun Karakter dan Etos Kerja Siswa SMKS Ar-Rahman - Intan, Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the implementation of the role of Islamic Religious Education (PAI) teachers in building students’ character and work ethic at SMK Ar-Rahman Medan. The research employed a qualitative approach through observation, interviews, and documentation at the partner school. The findings indicate that the implementation of educational policies is carried out through well-prepared planning, socialization, training, as well as continuous monitoring and evaluation. The curriculum applied integrates P5-based learning and deep learning, adjusted to each grade level through online, offline, and blended learning modes. PAI teachers adopt various strategies such as lectures, group discussions, Problem-Based Learning (PBL), and Project-Based Learning (PJBL), while also utilizing educational technology according to students’ majors. In developing religious character, discipline, and work ethic, the school provides strong support through programs such as Malam Bina Iman dan Takwa (MABIT), Qur’an learning, and the habituation of congregational prayers. The role of PAI teachers is evident in shaping students’ sense of responsibility, discipline, and motivation to learn through role modeling, habituation, and adaptive approaches to their psychological conditions. The results show significant impacts, including increased student awareness of discipline, communication ethics, responsibility, and self-control. Thus, the implementation of PAI teachers’ roles at SMK Ar-Rahman Medan proves to be significant in fostering Islamic character and a positive work ethic among students.